Efficient Synthesis of Functionalized Unsymmetrical Dialkyl Trisulfanes - Lach, Slawomir; Witt, Dariusz (Synlett, 2013)
We have developed a convenient method for the synthesis of functionalized unsymmetrical dialkyl trisulfanes under mild conditions in very good yields. The designed method is based on the reaction of (5,5-dimethyl-2-thioxo-1,3,2-dioxaphosphorinan-2-yl)-disulfanyl derivatives with alkyl disulfanyl anions generated in situ from S-acetyl disulfanyl derivatives and sodium methoxide. The developed method allows for the preparation of unsymmetrical trisulfanes bearing additional hydroxyl, carboxyl, or amino functionalities on both sides of the trisulfane functionality.
Keywords: unsymmetrical trisulfanes; thiols; hydrodisulfanes; S-acetyl alkyldisulfanes; phosphorodithioic acid